Zjawisko stresu w kontekście kultur organizacyjnych - Mróz, Joanna (Stress in the context of organizational culture, 2007)
The paper present the problem of stress in organizations. The author defines the article’s keywords and describes four types of organizational culture. Then follows the discussion on reasons of stress in different types of culture. Finally, the author points out methods of coping with stress in organizations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 123-132